Development of a Mitochondrial Myopathy‐Composite Assessment Tool. Issue 4 (30th August 2021) - Flickinger, Jean; Fan, Jiaxin; Wellik, Amanda; Ganetzky, Rebecca; Goldstein, Amy; Muraresku, Colleen C.; Glanzman, Allan M.; Ballance, Elizabeth; Leonhardt, Kristin; McCormick, Elizabeth M.; Soreth, Brianna; Nguyen, Sara; et al.
Abstract: Background: 'Mitochondrial Myopathy' (MM) refers to genetically‐confirmed Primary Mitochondrial Disease (PMD) that predominantly impairs skeletal muscle function. Validated outcome measures encompassing core MM domains of muscle weakness, muscle fatigue, imbalance, impaired dexterity, and exercise intolerance do not exist. The goal of this study was to validate clinically‐meaningful, quantitative outcome measures specific to MM. Methods: This was a single centre study. Objective measures evaluated included hand‐held dynamometry, balance assessments, Nine Hole Peg Test (9HPT), Functional Dexterity Test (FDT), 30 second Sit to Stand (30s STS), and 6‐minute walk test (6MWT). Results were assessed as z ‐scores, with < −2 standard deviations considered abnormal. Performance relative to the North Star Ambulatory Assessment (NSAA) of functional mobility was assessed by Pearson's correlation. Results: In genetically‐confirmed MM participants [ n = 59, mean age 21.6 ± 13.9 (range 7 – 64.6 years), 44.1% male], with nuclear gene aetiologies, n = 18/59, or mitochondrial (mtDNA) aetiologies, n = 41/59, dynamometry measurements demonstrated both proximal [dominant elbow flexion (−2.6 ± 2.1, mean z ‐score ± standard deviation, SD), hip flexion (−2.5 ± 2.3), and knee flexion (−2.8 ± 1.3)] and distal muscle weakness [wrist extension (−3.4 ± 1.7), palmar pinch (−2.5 ± 2.8), and ankle dorsiflexion (−2.4 ± 2.5)]. Balance [Tandem Stance (TS) Eyes Open (−3.2 ± 8.8, n = 53) and TS Eyes Closed (−2.6 ± 2.7, n = 52)] and dexterity [FDT (−5.9 ± 6.0, n = 44) and 9HPT (−8.3 ± 11.2, n = 53)] assessments also revealed impairment. Exercise intolerance was confirmed by strength‐based 30s STS test (−2.0 ± 0.8, n = 38) and mobility‐based 6MWT mean z ‐score (−2.9 ± 1.3, n = 46) with significant decline in minute distances (slope −0.9, p = 0.03, n = 46). Muscle fatigue was quantified by dynamometry repetitions with strength decrement noted between first and sixth repetitions at dominant elbow flexors (−14.7 ± 2.2%, mean ± standard error, SEM, n = 21). All assessments were incorporated in the MM‐Composite Assessment Tool (MM‐COAST). MM‐COAST composite score for MM participants was 1.3 ± 0.1 ( n = 53) with a higher score indicating greater MM disease severity, and correlated to NSAA ( r = −0.64, p < 0.0001, n = 52) to indicate clinical meaning. Test–retest reliability of MM‐COAST assessments in an MM subset ( n = 14) revealed an intraclass correlation coefficient (ICC) of 0.81 (95% confidence interval: 0.59–0.92) indicating good reliability. Conclusions: We have developed and successfully validated a MM‐specific Composite Assessment Tool to quantify the key domains of MM, shown to be abnormal in a Definite MM cohort. MM‐COAST may hold particular utility as a meaningful outcome measure in future MM intervention trials.